Mouse Models of Follicular and Papillary Thyroid Cancer Progression - Russo, Marika A.; Antico Arciuch, Valeria G.; Di Cristofano, Antonio (Frontiers in Endocrinology, 2012)
A significant number of well-differentiated thyroid cancers progress or recur, becoming resistant to current therapeutic options. Mouse models recapitulating the genetic and histological features of advanced thyroid cancer have been an invaluable tool to dissect the mechanisms involved in the progression from indolent, well differentiated tumors to aggressive, poorly differentiated carcinomas, and to identify novel therapeutic targets. In this review, we focus on the lessons learned from models of epithelial cell-derived thyroid cancer showing progression from hyperplastic lesions to locally invasive and metastatic carcinomas.